The Role of Police in Preventing the Regeneration of Armed Criminal Groups: A Study in Ilaga District - Oktovian Prawira Hidayat Siagian; Surya Nita; Zora A. Sukabdi (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
This study aims to analyze the extent of the role of education in deciding the regeneration of KKB criminal groups. The collaboration between the Puncak Regency Police and the Ilaga Regency Government in the implementation of education programs as an effort to prevent the regeneration of Armed Criminal Groups (KKB) shows positive potential in shaping the character and social awareness of the younger generation. This program that integrates the values of nationalism and ethics indirectly reduces the interest in recruitment by the KKB. This study uses a qualitative method with interview data collection techniques, observation and documentation. The results show that cross-sector synergy increases the effectiveness of planning, coordination, and implementation of educational programs, although it still faces challenges such as limited resources, infrastructure, and organizational cultural differences. Therefore, increasing human resource capacity, improving infrastructure, and making more adaptive policy adjustments are needed to optimize community support and program effectiveness. The findings of this study make an important contribution to the development of strategies to prevent KKB regeneration through continuous education.